2022
DOI: 10.21203/rs.3.rs-2261680/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A compendium of genetic regulatory effects across pig tissues

Abstract: The Farm animal Genotype-Tissue Expression (FarmGTEx, https://www.farmgtex.org/) project has been established to develop a comprehensive public resource of genetic regulatory variants in domestic animal species, which is essential for linking genetic polymorphisms to variation in phenotypes, helping fundamental biology discovery and exploitation in animal breeding and human biomedicine. Here we present results from the pilot phase of PigGTEx (http://piggtex.farmgtex.org/), where we processed 9,530 RNA-sequenci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 109 publications
(154 reference statements)
1
2
0
Order By: Relevance
“…1d), which may be caused by special transcriptome features of the reproductive cells. The above results showed that tissue differentiation is a major factor of transcriptome differentiation, which was consistent with the observation from other species, including humans, cattle, and pigs [10][11][12]34]. These results demonstrate that transcriptome similarity among tissues is associated with tissue biological function similarity.…”
Section: Tissue Differentiation Causes Different Gene Expression Pro Lessupporting
confidence: 90%
See 1 more Smart Citation
“…1d), which may be caused by special transcriptome features of the reproductive cells. The above results showed that tissue differentiation is a major factor of transcriptome differentiation, which was consistent with the observation from other species, including humans, cattle, and pigs [10][11][12]34]. These results demonstrate that transcriptome similarity among tissues is associated with tissue biological function similarity.…”
Section: Tissue Differentiation Causes Different Gene Expression Pro Lessupporting
confidence: 90%
“…It has been demonstrated that it can improve the genomics prediction accuracy when integrating TEGs into the genome prediction model for genomic selection breeding [9]. In mammals, genotype-tissue expression projects (GTEx) were characterized by integrating large-scale gene expression pro ling to gain insight into the transcriptions landscape and identify regulatory [10,[10][11][12]. Thus far, a large amount of RNA-Seq data for sorghum has been generated, however, rare efforts were made to comprehensively analyze the large collection of RNA-seq datasets to characterize the expression landscape in sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although 24,745 circRNAs were identified in this study, the data volume needs further supplementation. There are a large number of genomic data in pigGTEx, but circRNA research is still lacking [53]. In the future, we hope to include more data, such as pigGTEx data, in the circRNA analysis, aiming to discover more novel circRNAs and thus more comprehensively complement the circRNA data.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still some limitations in this study. Although Teng et al have demonstrated that tissue-specific factors have a greater influence in transcriptome analysis than sex, breeding, age, and other factors [53], we categorized these factors as batch effects in our study due to the absence of some annotation information in the data. This approach, as compared to individually correcting for each factor, may introduce some deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous international consortium projects, such as the Genotype-Tissue Expression (GTEx) [3] and the International Human Epigenome Consortium (IHEC) [4], have been initiated with the objective of establishing the correlation between genetic variation and gene expression in human tissues and deciphering the epigenetic regulation of cell states that are relevant to human health and disease. Recently, with technological advancement and data accumulation, integration of large-scale multi-omics data has gradually been applied in the field of agricultural animals, including the CattleGTEx Project [5], the PigGTEx Project [6] and the construction of multi-tissue gene expression atlases in beef cattle [7] and pigs [8].…”
Section: Introductionmentioning
confidence: 99%